MEMAHAMI SOSIALISASI KESETARAAN GENDER MELALUI MEDIA SOSIAL INSTAGRAM GIRL UP DIPONEGORO - Triswanti, Ririn; Sunarto, Sunarto; Hasfi, Nurul (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The phenomenon of gender inequality is still a problem in Indonesia. Girl Up Diponegoro emerged as a non-profit organization that carries out outreach with a focus on fighting for gender equality. This research aims to understand the socialization of gender equality through social media Instagram Girl Up Diponegoro from the administrator's perspective, including the socialization process, the urgency of each content, evaluation, and experiences while involved as an administrator and the perspective of understanding various content from the follower's perspective. This research uses a qualitative method with a critical phenomenological approach. The theory used in this research is Standpoint Theory. Retrieval techniques can be carried out using in-depth interviews, literature reviews, and documentation. The data obtained was then processed using phenomenological analysis including several stages, namely epoche process, transcendental phenomenological reduction, imaginative variation, synthesis of meanings and essence. The research results show that the process of socializing gender equality is carried out by highlighting various themes that are being widely discussed in society. Strategy for overcoming content that is difficult to disseminate by adapting the media and packaging it in scientific and easy-to-understand language. The urgency of every content uploaded is to provide education and awareness to the public regarding the problems that are currently occurring. Evaluation of success is seen from Instagram engagement and the management's ability to understand and open up discussion space for the content raised. The administrator joined Girl Up because of personal experiences of gender discrimination and because she feels she is a feminist. The administrators felt a change in themselves after joining as administrators with increased knowledge, self-confidence, and a better person as a person. From the perspective of followers who joined Girl Up Diponegoro because they are interested in gender equality, can understand the message content of various Girl Up content, there is content that makes followers feel impressive, and feel changes in themselves since following Girl Up Diponegoro Instagram with increased knowledge about gender equality, can better understand herself as a woman, and rise above feelings of insecurity. Overall, all informants conveyed their experiences with a perspective that challenged the dominance of women.